Ferumoxytol does not impact Standardized Uptake Values on PET/MR scans - Muehe, Anne M. (Mol Imaging Biol, 2020)
PURPOSE: Tumor response assessments on positron emission tomography (PET)/magnetic resonance imaging (MRI) scans requires correct quantification of radiotracer uptake in tumors and normal organs. Historically, MRI scans have been enhanced with gadolinium (Gd) based contrast agents, which are now controversial due to brain deposition. Recently, ferumoxytol nanoparticles have been identified as an alternative to Gd-based contrast agents, because they provide strong tissue enhancement on MR images but are not deposited in the brain. However, it is not known if the strong T1- and T2-contrast obtained with iron oxide nanoparticles such as ferumoxytol could affect MR-based attenuation correction of PET data. The purpose of our study was to investigate, if a ferumoxytol administration prior to a 2-deoxy-2-[(18)F]fluoro-D-glucose [(18)F]FDG PET/MR scan would change standardized uptake values (SUV) of normal organs. PROCEDURES: 30 pediatric patients (6-18 years) with malignant tumors underwent [(18)F]FDG-PET/MR scans (dose 3 MBq/kg). Fifteen patients received an intravenous ferumoxytol injection (5 mg Fe/kg) prior to the [(18)F]FDG-PET/MR scans (group 1). 15 additional age- and sex-matched patients received unenhanced [(18)F]FDG-PET/MR scans (group 2). For attenuation correction of PET data, we used a Dixon-based gradient echo sequence (TR 4.2 ms, TE 1. 1, 2.3 ms, FA 5), which accounted for soft tissue, lung, fat and background air. We used a mixed linear effects model to compare the tissue MRI enhancement, quantified as the signal-to-noise ratio (SNR), as well as tissue radiotracer signal, quantified as SUVmean and SUVmax, between group1 and group 2. Alpha was assumed at 0.05. RESULTS: The MRI enhancement of the blood and solid extra-cerebral organs, quantified as SNR, was significantly higher on ferumoxytol-enhanced MRI scans compared to unenhanced scans (p < 0.001). However, SUVmean and SUVmax values, corrected based on the patients body weight or body surface area, were not significantly different between the two groups (p > 0.05). CONCLUSION: Ferumoxytol administration prior to a [(18)F]FDG PET/MR scan did not change standardized uptake values (SUV) of solid extra-cerebral organs. This is important, because it allows to inject ferumoxytol contrast prior to a PET/MRI procedure and thereby, significantly accelterate image acquisition times.